(untitled) (Sains Humanika, 2017)
Engineering students often find their first university multivariable calculus experience very challenging. While moving from single variable function to multivariable function with procedural aspects of the subject, solving limit, derivation, and integral problems, they may struggle with crucial conceptual ideas underpinning them, making it very difficult to progress in more advanced courses. The main objective of this research is to establish a model of teaching and learning by integrating mathematical thinking and creative problem solving to support students in the learning of multivariable calculus through a blended learning environment. The results revealed that blended learning proved a valuable support and adjunct to studentsâ€™ learning.Â Â